Multicultural Education and Social Resilience in Finland's Diverse Society - Gunvor Hallström (CV Edujavare Publishing, 2026)
Multicultural education has become increasingly important in contemporary societies characterized by growing cultural diversity, migration, and globalization. Finland, traditionally perceived as a relatively homogeneous society, has experienced significant demographic changes that have transformed its educational and social landscape. This study examines the role of multicultural education in strengthening social resilience within Finland’s diverse society. Using a systematic literature review approach, the study synthesizes contemporary research on multicultural education, social resilience, intercultural competence, and inclusive education. The findings indicate that multicultural education contributes significantly to social resilience by promoting cultural understanding, social cohesion, inclusivity, and adaptive capacities among individuals and communities. Furthermore, multicultural educational practices encourage empathy, democratic participation, and intercultural dialogue, which are essential for addressing social challenges arising from increasing diversity. The study proposes a conceptual framework illustrating how multicultural education enhances social resilience through the development of intercultural competence and inclusive participation. The findings provide theoretical and practical insights for policymakers, educators, and institutions seeking to foster resilient and inclusive societies capable of adapting to social change while maintaining cohesion and collective well-being.